Saudi women behavior towards the acceptance of industrial small business - Bader Almohaimmeed; Ahmad Al-Tit; Abdel Hafiez Hasaballah (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The aim of this research was to canvass Saudi women's opinions about behavioral beliefs, i.e., attitudes, subjective norms and perceived behavioral control on their behavioral intention and hence adopting the small business initiative. Following the descriptive method, adopting the planned behavior theory PBT, a questionnaire consisted of 15 items was adapted to measure the variables of the research, i.e., three predictors, which are attitudes toward the behavior, subjective norms and perceived behavioral control, one mediating variable, which is behavioral intent and one dependent variable, which is the actual behavior. The questionnaire was electronically administered. A total of 724 questionnaires was collected in 2019. The results indicated that attitudes towards the behavior, subjective norms and perceived behavioral control had significant effects on behavioral intention, which in turn affect the target behavior. Behavioral intention had shown a mediating effect on the relationship between predictors and the response variable. Consequently, decision-makers are required to conduct awareness campaigns in order to promote the involvement in small businesses in the community, raising women's attitudes towards this type of business via success stories and full government support. Their perceived behavioral control can be enhanced through training to acquire business-related skills.
Keywords: J16; J18; J21; J22; J46; J71; J82; J83; D19; 650; planned behavior theory; Saudi women; industrial small business